2022
DOI: 10.1039/d1nj05235g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new 5,5′-dimethyl- and 5,5′-diphenylhydantoin-conjugated hemorphin derivatives designed as potential anticonvulsant agents

Abstract: Herein, the synthesis and characterization of some novel N-modified hybrid analogues of hemorphins containing a C-5 substituted hydantoin residue as potential anticonvulsants and for the blockade of sodium channels are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The test was conducted as described in our previous study [19]. In brief, an electric stimulus of 50 mA, 60 Hz, 0.2 s was applied individually to each tested mouse via corneal electrodes (Constant Current Shock Generator).…”
Section: Mes Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The test was conducted as described in our previous study [19]. In brief, an electric stimulus of 50 mA, 60 Hz, 0.2 s was applied individually to each tested mouse via corneal electrodes (Constant Current Shock Generator).…”
Section: Mes Testmentioning
confidence: 99%
“…Recently, we reported that newly synthesized peptide phenytoin derivatives exhibited anticonvulsant activity in several rodent tests [19]. In addition, the structure-biological activity relationship gave us the grounds to further characterize the novel 5,5′-diphenylhydantoins by incorporating some substituents into the N3 position of the hydantoin ring [20].…”
Section: Introductionmentioning
confidence: 99%
“…When a spinorphin molecule is mixed with structures that have been shown to have a biological effect, they work together to improve biological functions [ 9 ]. Phenytoin is a hydantoin-based anticonvulsant drug commonly used to inhibit the spread of seizures in the brain by reducing the excessive activation of neurons [ 18 ]. Research has shown that the compound affects the movement of substances across cell membranes, reducing the amount of sodium ions within the cell and causing hyperpolarization of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of biologically active compounds embedded in spirooxinole and hydantoin scaffolds prompted us to investigate further modifications within this class of compounds. Similarly, hydantoin derivatives (imidazolidine-2,4-diones) [28,29] emerged as privileged scaffolds in medicinal chemistry due to their various biological and therapeutic applications such as anticancer [30][31][32], anti-inflammatory [33][34][35], antidiabetic [36], anticonvulsant [37,38] and antimicrobial agents [39]. With such broad bioactivities, many hydantoin derivatives featured in several clinically used drugs such as phenytoin (anti-epileptic agent) [40], nilutamide (nonsteroidal androgen antagonists) [41] and nitrofurantoin (antibiotic for the treatment of infections caused by multi-drug resistant pathogens) (Figure 1) [42].…”
Section: Introductionmentioning
confidence: 99%